An integrated model of the knowledge antecedents for exploring software process improvement success. Issue 6 (20th April 2020) - Lee, Jung-Chieh; Shiue, Yih-Chearng; Chen, Chung-Yang
Abstract : Purpose: Software process improvement (SPI) is a knowledge activity that is critical to the excellence of information system development. This study observes two knowledge gaps in the quest for SPI success and proposes a research model that integrates existing knowledge antecedents to address these gaps. Based on organizational learning theory and the dynamic capability view, the proposed model consolidates a firm's absorptive capacity (AC), learning ability in terms of exploration and exploitation and knowledge sharing (KS), and it examines the contextual relationships among these knowledge antecedents on the path to SPI success. Design/methodology/approach: A quantitative research design is implemented to examine the model with a sample of 138 SPI-certified organizations in Taiwan and Mainland China. The partial least squares (PLS) technique is used for the data analysis. Findings: The results reveal the following findings. First, AC triggers the effect of exploration/exploitation on SPI success. Second, KS fosters exploitation but has an insignificant influence on exploration. Third, KS can promote AC, and it serves as the sourcing mechanism for all of the knowledge antecedents. Overall, an integrative set of knowledge learning routes is presented in guiding software firms on the way to SPI success. Originality/value: In addition to identification of the two knowledge gaps, this study advances the authors' understanding by comprehending the causal associations of the four knowledge antecedents on the way to SPI success.